Efeito da seca na dinâmica dos grupos funcionais fitoplanctônicos em reservatórios eutróficos do semiárido - Torres, Laíssa Macêdo (2014)
Reservoirs are the main sources of surface water in Brazil´s semiarid region. The majority of these water supplies, however, are compromised by eutrophication. A severe drought in 2012 contributed to significant losses in water volume, influencing the availability of resources (nutrients and light) for phytoplankton. The aim of this study is to understand the dynamics of the functional groups of phytoplankton and the factors that affect them during a severe drought in the semiarid reservoirs of the northeast. We therefore studied the Dourado, Gargalheiras and Passagem das Traíras reservoirs in Rio Grande do Norte from January 2012 to January 2013. The effect of drought favoured homogeneity within the reservoir, in relation to biotic and abiotic variables, notably the absence of water supply given the lack of flow from its tributaries (intermittent river). The phytoplankton functional groups of bloomforming cyanobacteria (SN, S1 and M) dominated throughout the year 2012, in both the shallow and deep areas of the three reservoirs studied. The groups were related to high concentrations of volatile solids, total phosphorus and ammonia, and high turbidity. Cylindrospermopsis raciborskii (SN group) was the species with the greatest biomass in the three reservoirs. M group (Sphaerocavum brasiliense) performed better in shallow waters with more available phosphorus. Our data showed that high concentrations of nutrients and low availability of light, besides the stability of the water column due to lack of flow and the system´s high residence time, favoured the dominance of bloom-forming cyanobacteria groups, especially those tolerant to shadow